Common File Formats. Issue 1 (26th March 2014) - Mills, Lauren
Abstract: An overview of the many file formats commonly used in bioinformatics and genome sequence analysis is presented, including various data file formats, alignment file formats, and annotation file formats. Example workflows illustrate how some of the different file types are typically used. Curr. Protoc. Bioinform . 45:A.1B.1‐A.1B.18. © 2014 by John Wiley & Sons, Inc.